Covid-19 and Forest Communities: Alignment and Challenges on Case Studies in Forest Community, Pemalang, Indonesia - Robert Siburian; Dicky Rachmawan; Fanny Henry Tondo (Forestry Faculty, Universitas Hasanuddin, 2022)
A pandemic, last seen a century ago, has reappeared in 2019 under the name of Covid-19. Poor forest communities are also especially affected by this pandemic. The qualitative method through literature and case study is used to explain the connection between the emergence of COVID-19, forest destruction, and its impact on the lives of people in forests in Indonesia. Two cases are going to be models of forest communities in Pemalang, namely LMDH Rawa Sakti and KTH GGL. The program was established by the Ministry of Environment and Forest (MoEF) to create a supportive atmosphere for forest communities’ survival to overcome the Covid-19 crisis. We use the new institutionalism concept introduced by Victor Nee (2003) to understand how the coupling within the affirmation concept was developed at micro-level in Indonesia. The result shows that there are unique and complex situations, especially between the social groups, the members (as the individual), and other actors that are not examined by new institutionalism, which are important to reach collective action or influence the situation. In the KTH GGL context, Juragan (as the other actor) determines the commodity although many members want to plant ginger that aligns with the Ministry of Environment and Forest’s suggestion. On the other hand, trust issues become a more important aspect for members of LMDH RS to do the group’s activity.